2016
DOI: 10.1177/0269215516673884
|View full text |Cite
|
Sign up to set email alerts
|

Is there a difference in physical activity levels in patients before and up to one year after unilateral total hip replacement? A systematic review and meta-analysis

Abstract: Objective:To determine the difference in physical activity levels before and up to one year after unilateral primary total hip replacement.Data sources:A search was performed on 13 July 2016. Studies were eligible for inclusion if they presented preoperative and up to one year postoperative measures of physical activity for patients who had undergone unilateral primary total hip replacement.Review methods:Any article that used a measure of physical activity pre and up to one year post-unilateral primary total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
(78 reference statements)
1
24
0
Order By: Relevance
“…A specific focus of our research frame is the elderly, as there are major concerns about functional recovery and length of hospital stay in this sub-population. This intension was firstly determined from the examination of previous literature, where heterogeneity of population characteristics compromised the internal consistency of results of systematic reviews and meta-analyses [5]. The primary endpoint is to clarify the impact of specific training on subjective and objective surgical outcomes; the secondary endpoint focuses on the influence on postoperative parameters including the length of hospitalization and the quality of life of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…A specific focus of our research frame is the elderly, as there are major concerns about functional recovery and length of hospital stay in this sub-population. This intension was firstly determined from the examination of previous literature, where heterogeneity of population characteristics compromised the internal consistency of results of systematic reviews and meta-analyses [5]. The primary endpoint is to clarify the impact of specific training on subjective and objective surgical outcomes; the secondary endpoint focuses on the influence on postoperative parameters including the length of hospitalization and the quality of life of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…This has been promoted more recently in Enhanced Recovery after Surgery programmes, where there is an additional emphasis on enabling a patient to return to work, activities of daily living and pre-surgery function [6]. There is evidence to suggest that physical activity levels do not increase after surgery [7], and in some cases, patients are less active at 2-year follow-up than before hospital admission [8•]. As return to normal function becomes the benchmark for recovery after major surgery, a focus of perioperative care should now be on post-discharge support and physical rehabilitation strategies [9•].…”
Section: Introductionmentioning
confidence: 99%
“…The attractor index in our patients was below the fatigue index cut-off for motor fatigue (δ F = 4) reported by Sehle et al ( 2014 ). Because we limited the walking exercise to 6 min based on the widely accepted use of the 6MWT in clinical cohorts (Gao et al, 2014 ; Dunn et al, 2015 ; O'Brien et al, 2016 ; Keilani et al, 2017 ; Withers et al, 2017 ), it is remarkable that we still observed greater changes in attractor variability in patients than in healthy persons. It is unknown if patients in our study would have experienced even greater changes in attractor variability if they would have continued to walk until exhaustion or inability to continue due to sLSS symptoms.…”
Section: Discussionmentioning
confidence: 99%